Jasmonates: biosynthesis, perception, signal transduction and action in plant stress response, growth and development. An update to the 2007 review in Annals of Botany - Wasternack, C.; Hause, B. (Annals of botany, 2013)
• Background Jasmonates are important regulators in plant responses to biotic and abiotic stresses as well as in development. Synthesized from lipid-constituents, the initially formed jasmonic acid is converted to different metabolites including the conjugate with isoleucine. Important new components of jasmonate signalling including its receptor were identified, providing deeper insight into the role of jasmonate signalling pathways in stress responses and development. • Scope The present review is an update of the review on jasmonates published in this journal in 2007. New data of the last five years are described with emphasis on metabolites of jasmonates, on jasmonate perception and signalling, on cross-talk to other plant hormones and on jasmonate signalling in response to herbivores and pathogens, in symbiotic interactions, in flower development, in root growth and in light perception. • Conclusions The last few years have seen breakthroughs in the identification of JASMONATE ZIM DOMAIN (JAZ) proteins and their interactors such as transcription factors and co-repressors, and the crystallization of the jasmonate receptor as well as of the enzyme conjugating jasmonate to amino acids. Now, the complex nature of networks of jasmonate signalling in stress responses and development including hormone cross-talk can be addressed.